Visualización y memorialización de los defensores y defensoras de los derechos humanos en Ecuador a través del diseño gráfico y la caracterización de personajes - Guerra Proaño, Arleth Adem (2021)
Dealing with social events of great impact in the country is something very sensitive, even more so when different actors, both political and cultural, are involved. This gives way to speculation of comments out of place and even when the main causes or reasons for the events are not known, a wave of hatred is created due to misunderstandings resulting in a distancing of social unity. The purpose of this research is to recognize the importance of the indigenous movement as a cultural and decisive actor in the plurinational and pluricultural strengthening of Ecuador. Several indigenous leaders in charge of being the spokespersons of the struggle of their people are highlighted, as well as the causes and rationale of each mobilization since the First Great Indigenous Uprising in 1990 until the year 2019. From this, a tribute of honor is given for each struggle for Human and Collective Rights, as well as for each achievement obtained for a better development of the country in the course of the 30 years of struggle. It is important to mention the relevance of this research study because it will contribute to a progressive and educational solution, taking the role of informing and expanding the cultural vision and understanding from another perspective the importance of the indigenous movement. All this supported by Graphic Design as a means of developing a graphic proposal with visual impact.